Cavity with distributed dielectric coating for subterahertz second-harmonic gyrotron - Shcherbinin, V.I.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2016)
Metallic cavity with distributed dielectric coating for the 0.4 THz second harmonic gyrotron is proposed and
studied using the generalized scattering matrix approach. It is shown that such coating provides several-fold increase
in the Q-value of the operating mode with respect to that of the fundamental competing mode at a reasonable level
of ohmic losses, dielectric losses and mode conversion. Металлический резонатор с распределённым диэлектрическим покрытием предложен для использования
в 0,4 ТГц гиротроне на второй гармонике гирочастоты и исследован с помощью обобщённого метода мат-
рицы рассеяния. Показано, что такое покрытие позволяет в несколько раз увеличить добротность рабочей
моды гиротрона по сравнению с добротностью конкурирующей фундаментальной циклотронной моды при
приемлемом уровне омических потерь, потерь в диэлектрике и конверсии мод. Металевий резонатор з розподіленим діелектричним покриттям запропоновано для використання в
0,4 ТГц гіротроні на другій гармоніці гірочастоти та досліджено за допомогою узагальненого методу матри-
ці розсіювання. Показано, що таке покриття дозволяє в кілька разів збільшити добротність робочої моди у
порівнянні з добротністю конкуруючої фундаментальної циклотронної моди при прийнятному рівні омічних
втрат, втрат у діелектрику та конверсії мод.